The Denmark Vesey Affair : A Documentary History - Miller, Randall M.; Harrold, Stanley; Paquette, Robert L., 1951-; Egerton, Douglas R. (Book collections on Project MUSE., 2017)
Egerton and Paquette have edited and annotated a wealth of archival material to create the authoritative one-volume documentary history of the Denmark Vesey insurrection of 1822.